Developing Narrative Writing Skills Through The Learning Method of Grouping Ideas (Clustering) Using Photographic Images by Student UPTD SMP Negeri 1 Silau Laut Asahan - Zahrilla, Zahrilla; Sutikno; Rahmat Kartolo (PT Inovasi Pratama Internasional, 2026)
In the world of education, writing skills are one of the important aspects that must be mastered by students to support overall language skills. This study aims to improve the ability of class VIII students of UPTD SMP Negeri 1 Silau Laut Asahan Regency in writing narrative essays through the application of the learning method of grouping ideas (clustering) using photographic image media. The main problem identified is the low writing skills of students, which is caused by ineffective learning methods and low student interest in writing activities. The method used is Classroom Action Research (CAR), implemented in three cycles covering the stages of planning, implementation, observation, and reflection. The subjects of the study consisted of 42 students of grade VIII. Data were collected through writing tests, observations, and interviews, and analyzed descriptively quantitatively and qualitatively. The results of the study indicate that the application of the clustering method based on photographic images succeeded in gradually improving students' writing skills. In the pre-cycle stage, students' learning completeness was only 35%, with a relatively low level of ability. After the application of the method, students' completeness increased to 54.76% in cycle I, 69.04% in cycle II, and reached 90.47% in cycle III. Improvements were seen in the ability to determine the main idea, organize the storyline, choose diction, and use the narrative structure correctly. This study concludes that the idea of grouping method (clustering) based on photographic image media is effective in improving students' narrative writing skills. In addition to encouraging creativity, this method also creates a more active and enjoyable learning atmosphere. This study is expected to be a reference in developing innovative learning strategies to improve students' writing skills